Autoria de cenários openflow utilizando visual network description (versão SDN) - FONTES, Ramon dos Reis (2013)
The demand for sending, querying and receiving information, e.g. text, images, audio or video, is growing exponentially and since Internet was not designed to meet this demand, issues such as vulnerability, instability, scalability and incompatibilities are more evident as well. The success of Internet is undeniable, however some of its limitations are being unveiled, thus it is important to reconsider its architecture and main protocols. For this reason, experimental networks arise as a solution for the simulation of new proposals. In this context, the concept of Software Defined Networks was conceived, and in particular the OpenFlow protocol, where software is responsible for steering the behavior of the network. When applied to experimental networks, network management tools are also useful since they provide a detailed view of a network, thus allowing its optimization. Therefore, different tools can be applied, such as tools responsible for building the topology, monitoring, simulation and analysis. Nevertheless, these tools in general lack interoperability. As a solution to this problem, the utilization of the NSDL Framework is proposed for providing the interoperability among heterogeneous tools, allowing thus the communication between different network management tools. Nevertheless the main goal of this work is the extension of the graphical authoring tool so-called Visual Description Network, originally proposed for the authoring of traditional and wireless network scenarios, in order to also support the authoring of software defined networks scenarios. As a main result, the graphical tool Visual Network Description - VND (SDN version) was conceived. Besides the authoring of OpenFlow scenarios, the VND (SDN version) also allows the automatic generation of NSDL descriptions and scripts in order to enable their subsequent integration with other OpenFlow compliant tools. To illustrate the authoring with VND and execution of OpenFlow scenarios, four case studies were conducted. One of the main advantages of this tool, besides its simplicity, is its flexibility for the customization of objects and parameters that can be manipulated during the creation of network scenarios.